Analysis of The Effect of Credit Default Swap and Macroeconomic Variables on Indonesian Government Bonds Yield - Alfiana Alfiana; Wenny Desty Febrian; Suwarsito; Herawati; Aprih Santoso (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The objective of this study is to examine the long- and short-term relationships between macroeconomic variables such as inflation, the Bank Indonesia interest rate (BI Rate), the USD/IDR exchange rate, gross domestic product (GDP), and Credit Default SWAP on Indonesian sovereign bond yields from January 2016 to December 2022. The Vector Error Correction Model (VECM) analysis is employed. Microsoft Excel and Eviews were used to perform the research. According to the findings, the dependent variable, inflation, does not have a long-term relationship with bond yields of five, ten, fifteen, or twenty years, but does have a short-term relationship with bond yields. BI Rate has a positive long-term relationship with bond yields of five, ten, and fifteen years. USD/IDR Exchange Rate has a negative long-term relationship with government bond yields of all tenors. Gross Domestic Product (GDP) has a negative long-term relationship with bond yields